ANALISIS PENGENDALIAN KUALITAS PRODUK GOLF GLOVE MENGGUNAKAN METODE PDCA DENGAN PENDEKATAN STATISTICAL QUALITY CONTROL (SQC) PADA CV. CAHAYA SETIA MULIA ABADI - Fachrizal Nazir; Suseno Suseno (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract: Product quality is a key factor in achieving customer satisfaction and enhancing a company's competitiveness. CV. Cahaya Setia Mulia Abadi, a manufacturer of golf gloves, continues to experience a product defect rate of 12.06%, indicating the need for a systematic quality control approach. This study aims to identify the types and causes of product defects and propose improvement strategies using the Plan-Do-Check-Act (PDCA) method supported by the Statistical Quality Control (SQC) approach. The Plan stage employed quality control tools, including check sheets, P-Charts, Pareto diagrams, and Fishbone diagrams, while the Do, Check, and Action stages were used to develop improvement proposals through the 5W+1H matrix and the preparation of Standard Operating Procedures (SOPs). The results revealed three major defect types: holes (55%), remaining threads (30%), and cutting defects (15%). The P-Chart analysis indicated that the production process was not yet fully under, while the Fishbone analysis identified human, machine, method, material, and work environment as the primary causes of defects. The proposed improvements include developing SOPs, strengthening production supervision, implementing regular machine maintenance, improving raw material quality control, and standardizing work methods. Therefore, the implementation of the PDCA method supported by SQC effectively identified the root causes of product defects and provided improvement recommendations to support continuous product quality improvement. Keywords: Quality Control, PDCA, Statistical Quality Control (SQC), control chart, Pareto diagram, Fishbone diagram.